The Influence of Fanaticism and Religiosity on Verbal Aggressive Behavior Among K-Pop Fans - Khairani, Miftahul; Desky, Ahmed Fernanda (Prodi Studi Agama-Agama, 2025)
This study aims to examine the influence of fanaticism and religiosity on verbal aggression among K-pop fans, particularly EXO-L fans in Medan City. A quantitative survey approach was used, involving 55 respondents as the research sample. Data were collected using questionnaires and analyzed with SPSS version 25 to assess the relationships between fanaticism (X1), religiosity (X2), and verbal aggression (Y). The results indicate that fanaticism has a significant correlation with verbal aggression, with a correlation coefficient of 0.508, while religiosity also shows a significant correlation with a coefficient of 0.550. Furthermore, a significant combined relationship was found between fanaticism and religiosity with verbal aggression, with a correlation coefficient of 0.685. This study concludes that fanaticism toward K-pop idols can drive aggressive behaviors, including verbal aggression, especially when idols or fan communities are perceived as being attacked. Religiosity, on the other hand, has a dual role: it can mitigate aggression through spiritual self-control or trigger aggression when religious values are perceived to be threatened by K-pop culture.